Direct spinning of CNT fibres: Past, present and future scale up. (November 2019) - Smail, Fiona; Boies, Adam; Windle, Alan
Abstract: It is now 14 years since the publication of the first paper describing the continuous production of carbon nanotube fibres by the direct spinning process. Since then much effort and numerous papers have focused on optimisation of lab-scale spinning process and product properties. To some extent structure-property type research has outstripped studies to understand and eventually scale up the production process itself. Progress is such that the axial mechanical strength and stiffness of carbon nanotube fibres are already competing with other high performance fibres such as aramid, polyethylene and carbon, while both the electrical and thermal conductivities are one to two orders of magnitude better than PAN based carbon fibre. However, to undercut other high performance fibres on price while at the same time providing a wider ranging property spectrum, requires scale-up, although comparatively few publications in the literature have focused on this. Here the various key parameters which will come to bear during large-scale plant design are addressed, especially those associated with hydrogen supply and management. A vision of a 150 tonne per year plant is provided (Fig 9), but the vision is just that, and must be seen as informed speculation. Graphical abstract: Image 10699